Lactente com Angina de Ludwig complicada: um relato de caso - Mariana Digiovanni Pechebea; Angelica Maria Moro Ozosco; Ana Paula Cauduro Couto; Carolina Oliveira de Paulo; Diana Lorena Garavito Ramirez; Luiza Valentim Centenaro; Wendell Paiva Vita (Residência Pediátrica)
Ludwigs angina is a severe and rapidly progressive infection that involves sublingual, submental or submandibular space, and can occur unilaterally or bilaterally. Its more frequent in male sex and in the fourth decade of life. Any recent infection or injury to the area may predispose this disease. The diagnosis is clinical and should be considered in any patient with a history of fever associated, stiff neck, induration and local edema. The mortality rate can exceeded 50% if the diagnosis is late. Treatment is based on early recognition, intravenous antibiotic therapy and ensuring a patent airway. This report presents the case of an infant with complicated Ludwigs angina.